POLITICAL LITERACY AND DEMOCRATIC UNDERSTANDING IN ISLAMIC HIGHER EDUCATION: EVIDENCE FROM URBAN MUSLIM STUDENTS AT UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG - Agustam, Agustam; Cleo Phattra, Hellint; Syakir Mohd Rosdi, Mohd; Hawari, Nadirsah; Yudha, Gesit (AKADEMIKA: Jurnal Pemikiran Islam, 2026)
This study aims to examine the influence of political literacy on students’ understanding of democracy among students enrolled in the Islamic Political Thought Study Program at a  State Islamic University in Lampung in 2024. The study is grounded in the theoretical assumption that political literacy functions as a form of civic competence that shapes students’ capacity to understand, evaluate, and internalize democratic values and practices. This research employed a quantitative survey design using a questionnaire as the primary instrument to measure political literacy as the independent variable and understanding of democracy as the dependent variable. The population consisted of active students of the Islamic Political Thought Study Program at Universitas Islam Negeri (UIN) Raden Intan Lampung, with 20 respondents selected through purposive sampling. Data were analyzed using simple linear regression to examine the direction and magnitude of the relationship between the two variables. The results show that political literacy has a positive and statistically significant effect on students’ understanding of democracy (p < 0.05), indicating that students with higher political literacy tend to demonstrate better understanding of democratic values, participation, and public accountability. The coefficient of determination (R²) further indicates that political literacy contributes meaningfully to explaining variation in students’ democratic understanding, although the remaining variance is influenced by factors outside the model. These findings highlight the importance of strengthening political literacy through curriculum development, student organizational engagement, and civic learning in Islamic higher education. This study contributes empirically to the development of political education research by demonstrating that political literacy plays a significant role in shaping democratic understanding among students in an Islamic academic context.